Building Construction Characteristics of Stone Masonry Houses in Peru - (:unkn) unknown (Springer Nature Switzerland, 2024)
In Peru, the construction with stone masonry has been well studied, mainly focused on archaeological heritage. However, little attention has been given to the existing stone houses, which comprise almost 2% (120,000 units) of the country's total dwelling...
Keywords: Mampostería de piedra; Construcción